Challenges for the adoption of model-driven web engineering approaches in industry - Robles Luna, Esteban (2018)
Model-Driven Web Engineering approaches have become an attractive research and technology solution for Web application development. However, for more than 20 years of development, the industry has not adopted them due to the mismatch between technical versus research requirements. In the context of this joint work between academia and industry, the authors conduct a survey among hundreds of engineers from different companies around the world and, by statistical analysis, they present the current problems of these approaches in scale. Then, a set of guidelines is provided to improve Model-Driven Web Engineering approaches in order to make them viable industry solutions.